2015
DOI: 10.1002/brb3.420
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive decision making as a gradual process: investigating semantic intuition‐based and priming‐based decisions with fMRI

Abstract: IntroductionIntuition has been defined as the instantaneous, experience‐based impression of coherence elicited by cues in the environment. In a context of discovery, intuitive decision‐making processes can be conceptualized as occurring within two stages, the first of which comprises an implicit perception of coherence that is not (yet) verbalizable. Through a process of spreading activation, this initially non‐conscious perception gradually crosses over a threshold of awareness and thereby becomes explicable.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 75 publications
(167 reference statements)
0
26
0
2
Order By: Relevance
“…In other words, people were intuitively sensitized to the detection of coherence prior to its explicit recognition (i.e., before having an explicit insight into the underlying semantic structure). Using a similar task, which consists of up to 15 semantically target-related clue words (i.e., the Accumulated Clues Task), it could be observed that participants continuously approached the explicit representation of environmental patterns/meaning ( Bowers et al, 1990 ; Reber et al, 2007 ), which could be recently also demonstrated on a neuronal level when using the semantic coherence task ( Zander et al, 2015 ). These results are perfectly in line with Bowers et al (1990) definition of intuition and the corresponding gradual two-stage model.…”
Section: Differences In the Cognitive Processes Assumed To Underlie Imentioning
confidence: 98%
See 1 more Smart Citation
“…In other words, people were intuitively sensitized to the detection of coherence prior to its explicit recognition (i.e., before having an explicit insight into the underlying semantic structure). Using a similar task, which consists of up to 15 semantically target-related clue words (i.e., the Accumulated Clues Task), it could be observed that participants continuously approached the explicit representation of environmental patterns/meaning ( Bowers et al, 1990 ; Reber et al, 2007 ), which could be recently also demonstrated on a neuronal level when using the semantic coherence task ( Zander et al, 2015 ). These results are perfectly in line with Bowers et al (1990) definition of intuition and the corresponding gradual two-stage model.…”
Section: Differences In the Cognitive Processes Assumed To Underlie Imentioning
confidence: 98%
“… Bowers et al (1990) approach is not only theoretically important it also carries paradigmatic weight. In order to empirically test their model’s assumptions, the authors developed several novel paradigms (verbal as well as perceptual ones), which today, after slight revisions, belong to the standard paradigms of intuition research (e.g., Bolte and Goschke, 2005 ; Volz and von Cramon, 2006 ; Topolinski and Strack, 2009b ; Hicks et al, 2010 ; Remmers et al, 2014 ; Zander et al, 2015 ). One of them is the semantic coherence task mentioned above, consisting of word triads that can be either semantically coherent (e.g., SALT, DEEP, and FOAM) or incoherent (DREAM; BALL; BOOK).…”
Section: Differences In the Cognitive Processes Assumed To Underlie Imentioning
confidence: 99%
“…The semantic coherence task (i.e., the triads task) used in this study dates back to Bowers et al (1990) and has been frequently used to study intuitive processing (e.g., Bolte & Goschke, 2005;Remmers et al, 2014;Topolinski & Strack, 2009a;Zander et al, 2015). For each trial of the task, participants were presented with word triads (i.e., three words at once presented below each other) that-unbeknownst to them-could be either semantically coherent or incoherent.…”
Section: Coherence Judgment Taskmentioning
confidence: 99%
“…Such a belief may have played a role in Experiments 1 and 2, because rated pairwise relatedness between triad words was higher for coherent than for incoherent triads (cf. Zander, Horr, Bolte, & Volz, 2015). In Experiment 3, we used coherent and incoherent triads that did not differ in pairwise relatedness.…”
Section: Methodsmentioning
confidence: 99%